Implementation of production principles of islamic economics in Putra Mandiri Fish Business in Semarang City - Nur Burhanuddin; Anton Bawono (Enrichment : Journal of Management, 2022)
In an effort to improve the welfare of a country, good production is needed where it does not disrupt the sustainability of natural resources and maintain social ethics. Good production activities can be carried out through the implementation of principles of the Islamic economy, but not all Muslim producers have implemented the principle. The purpose of the study is to analyze the implementation of the principles of Islamic economics in the fish production company "Putra Mandiri" at Semarang city. The research method employed is qualitative research, which in this method analyzes and presents a systematic field fact that finally can be easier to understand and deduced by current guidelines. The results of this study are that the fish production company "Putra Mandiri" implemented the principles of the Islamic economy that have been well carried out, proven by the volume of sales at the time of the covid-19 pandemic. It's worth keeping the sales volume going up.